COMPARISON OF EFFICACY OF TWO DIFFERENT DOSES OF FAMCICLOVIR IN THE PREVENTION AND TREATMENT OF POSTHERPETIC NEURALGIA - Sharif, Shawana; Aslam, Faiza; Faisal, Lubna Rani; Saleem, Muhammad Amer (Journal of Ayub Medical College Abbottabad, 2019)
Background: Herpes Zoster is a common dermatological ailment. Various treatment modalities are in use for prevention of Post Herpetic Neuralgia (PHN) which is the most common complication of herpes zoster. Our study aimed to compare the efficacy of famciclovir 250 mg versus 500 mg in this regard. Methods: The study was conducted at a tertiary care hospital recruiting subjects by using simple random sampling, group A patients received famciclovir 250 mg thrice daily for 1 week while group B patients were administered 500 mg. Follow ups were arranged at 2, 4 & 12 weeks. Efficacy was assessed by pain evaluation as per numeric rating scale and counting number of skin lesions. PHN was taken as persistent pain at 4 weeks follow up. All the statistical analysis was done using SPSS. Results: A total of 30 patients were included in the study with each group (A & B) containing 15 patients each. Both dosing groups were statistically consistent with each other in reducing pain at 2, 4 and 12 weeks follow up. Skin lesions were not observed after 2 weeks in either group. The median of difference of pain scores at 2 weeks was similar as at 4 weeks. Conclusion: Famciclovir 250 mg thrice daily for one week is equally effective as 500 mg in treating active herpes zoster and prevention of PHN. However, long term follow-up is required for assessing the true incidence of PHN. Keywords: Herpes Zoster; Famciclovir; Efficacy; Neuralgia; Postherpetic